Measuring service quality and performance towards customers' perceptions: a study on parents' perception of public school in Kuching division / Abdul Aziz Ahmad - Ahmad, Abdul Aziz (2010)
This study explores and describes the perceptions and expectations of Kuchingities parents concerning reliability and effectiveness of education provided by public school in Kuching, Sarawak. The study will specifically focus on parents and students of Kuching division. This paper will look into areas like potential influences of social and cultural elements on the parents' perceptions and in doing so, challenges the current notion of what constitutes 'appropriateness' in early childhood education. Lately, Malaysian parents, in general, are relatively concern over the quality of education their children are receiving in the era of stiff competition in the job market as well as globalisation, and concerns also expressed on whether the existing education system, quality wise, is able to meet the current and future needs of Malaysian society as a whole. This model may be a useful one for exploring perceptions in future studies. The history of Education in Malaysia began as early as the 19th century. Straits Settlement was among the first few states that witness the setting up of what is called as the father of modem school in Malaysia. Penang Free School which was initiated by a Missionary group in early 19th century is among the earliest modem school being set up in Malaya and British Borneo.